Admission Policies of Labor Unions - Summers, Clyde W. (Quarterly Journal of Economics, 1946)
Introduction, 66. — Constitutional provisions and union practices: exclusion because of race, 67; exclusion because of citizenship, 72; because of political affiliations or beliefs, 75; because of creed, 76; because of sex, 77; closed unions, 78. — Exclusionary devices: initiation fees, 80; apprenticeship requirements, 82; competency tests, 83; license laws, 83; permit cards, 84. — Why do unions deny the right to join? 84. — Economic limitations on exclusionary policies, 89. — Conclusions, 91.